A comparison of ultrasound-guided erector spinae plane block and epidural anesthesia for postoperative recovery in elderly individuals following laparoscopic gastrectomy: a randomized controlled trial - Cancan Wang; Jie Song; Song Tong; Yun Li; Jin Jiang; Minghan Sheng; Xianwen Hu (BMC Anesthesiology)
Abstract Background Erector spinae plane block (EspB) is increasingly being applied for laparoscopic radical gastrectomy as an analgesic supplement to general anesthesia. The aim of this study was to evaluate the analgesic efficacy and postoperative recovery outcomes of EspB and epidural anesthesia (EDA) in elderly patients (above 65 years-of-age) undergoing laparoscopic gastrectomy in order to determine the precise multimodal analgesia (PMA) that promotes postoperative recovery. Methods In total, 102 patients assigned for elective laparoscopic gastrectomy were classified into three groups: preoperative bilateral EspB with general anesthesia, EDA with general anesthesia, and general anesthesia alone. The primary outcome, quality-of -recovery (QoR), was evaluated by the QoR-15 questionnaire at T1 (24 h postoperatively). Secondary endpoints included pain scores; postoperative recovery at T0 (1 day before surgery), T2 (3 days postoperatively), and T3 (7 days postoperatively); intraoperative hypotension; opioid consumption; gastrointestinal recovery; and side effects. Results QoR-15 scores for both EspB and EDA were significantly higher than that for general anesthesia alone at T1 (112.09 ± 6.56 and 110.32 ± 5.51a vs. 102.74 ± 4.91 P < 0.001) and T2 (114.79 ± 5.69 and 114.62 ± 6.24 vs. 110.85 ± 4.49 P < 0.05). In addition, both EspB and EDA reduced VAS scores with regards to resting and activity pain at T1(4 ( 2 ) vs. 4 ( 2 ) vs. 4.5 ( 1 ) and 4 ( 1 ) vs. 4( 1 ) vs. 5 ( 1 ), respectively P < 0.05). EspB was associated with reduced postoperative nausea and vomiting than EDA (P < 0.05). Conclusion EspB provides effective analgesia with fewer side effects, such as nausea and vomiting, compared to EDA, and may be a valuable component of multimodal analgesia for improving postoperative recovery in elderly patients undergoing laparoscopic gastric cancer surgery with general anesthesia. Trial registration chictr2400079956 (January 17, 2024).